Leadership of Religious Leaders in the Framework of Religious Moderation in Strengthening Community Social Cohesion - Abidin, Achmad Anwar; Fatawi, Izzul (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
The purpose of this research is to describe the leadership of religious leaders who are members of the Religious Harmony Forum in strengthening religious moderation and strengthening social cohesion of the community in Jombang district. The research subjects were 17 religious leaders who were members of the Religious Harmony Forum in Jombang Regency, East Java. The research method used in this study is a qualitative method with a case study approach. It was found that religious leaders in Jombang district have a moderate view in religion and have a strong commitment to increasing social cohesion between religious communities. However, there are several needs that must be met to strengthen the role of these figures, such as adequate budget support, a strong legal umbrella, increased frequency of socialization and education, and better appreciation and support from local governments. By meeting these needs, it is hoped that their leadership will be more effective in carrying out their duties and achieving the goal of religious moderation in Jombang Regency in creating harmony between religious communities.